Characterisation of Australian Verdelho wines from the Queensland Granite Belt region. (1st April 2016) - Sonni, Francesca; Moore, Evan G.; Chinnici, Fabio; Riponi, Claudio; Smyth, Heather E.
Highlights: The Queensland Verdelho volatile profile has been characterised for the first time. A sensory descriptive analysis has also been undertaken for these wines. SPE–GC/MS analysis identified key compounds contributing to Verdelho flavour. Sensory descriptive analysis underlined characteristic attributes for the wines. These results lay the foundation for further study of Verdelho as a dry wine style. Abstract: Verdelho is a white-grape-vine, growing well in the Granite Belt region of Queensland. Despite its traditional use in Madeira wine production, there is scant literature on the flavour characteristics of this variety as a dry wine. In this work, for the first time, volatile compounds of Verdelho wines from the Granite Belt have been isolated by solid phase extraction (SPE), and analysed using gas chromatography–mass spectrometry (GC–MS). A corresponding sensory characterisation of this distinctive wine style has also been investigated, using sensory descriptive analysis. Chemical compounds that mostly contribute to the flavour of these wines were related to fruity sweet notes (ethyl esters and acetates), grassy notes (3-hexenol), floral aromas (2-phenylethanol and β-linalool) and cheesy aromas (fatty acids). Sensory analysis confirmed that the Verdelho wines were characterised by fruity aroma attributes, especially "tree-fruit" and "rockmelon", together with "herbaceous", while significant differences in the other attributes were found.